2013
DOI: 10.2113/econgeo.108.8.1813
|View full text |Cite
|
Sign up to set email alerts
|

Origin of PGE-Depleted Ni-Cu Sulfide Mineralization in the Triassic Hongqiling No. 7 Orthopyroxenite Intrusion, Central Asian Orogenic Belt, Northeastern China

Abstract: The ~216 Ma Hongqiling No. 7 intrusion is located in the southern margin of the Central Asian orogenic belt, northeastern China. It was the second largest Ni producer after Jinchuan in China. The intrusion crops out in an area of ~0.013 km 2 on the surface. It intruded gneisses and marbles of the Paleozoic Hulan Formation. The intrusion is mainly composed of orthopyroxenite (~95 vol %), with minor harzburgite and norite. Over 90 vol % of the intrusion contains disseminated, net-textured or massive sulfides. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…11a), which also indicates crustal contamination. This conclusion is further supported 292 by initial 187 Os/ 188 Os ratios (0.34 to 3.02) measured in the Hongqiling ore rocks and reported by 293 previous workers (Wei et al 2013;Sun 2013a;Hao et al 2014b). The values of 187 Os/ 188 Os are much higher than those of Cu-Ni sulfide deposits free of crustal contamination (e.g.…”
Section: Fractional Crystallization and Crustal Contaminationsupporting
confidence: 72%
See 1 more Smart Citation
“…11a), which also indicates crustal contamination. This conclusion is further supported 292 by initial 187 Os/ 188 Os ratios (0.34 to 3.02) measured in the Hongqiling ore rocks and reported by 293 previous workers (Wei et al 2013;Sun 2013a;Hao et al 2014b). The values of 187 Os/ 188 Os are much higher than those of Cu-Ni sulfide deposits free of crustal contamination (e.g.…”
Section: Fractional Crystallization and Crustal Contaminationsupporting
confidence: 72%
“…This trace element characteristics of the Hongqiling ore-bearing intrusions suggest that Hongqiling ore-bearing intrusions experienced the low-grade metamorphism or hydrothermal alteration. In addition, the Pd/Ir ratios of Hongqiling rocks are very low (Wei et al 2013;Hao et al 2014b), also suggesting hydrothermal alteration had a very small impact on the Hongqiling ore-bearing intrusions. Based on the mobility of elements, we choose HFSEs and REEs (e.g.…”
Section: Effect Of Alterationmentioning
confidence: 99%
“…1a, the southern part of the Central Asian Orogenic Belt contains magmatic sulfide deposits formed in a subduction setting such as the Beiligaimiao deposit (this study) and the Erbutu deposit (Peng et al, 2013) in the central region, and post-subduction setting such as the Huangshandong deposit in the western region (Mao et al, 2014) and the Hongqiling No.7 deposit in the eastern region (Wei et al, 2013).…”
Section: Resultsmentioning
confidence: 83%
“…Previous studies revealed that the Late Triassic maficultramafic intrusions (e.g., Nos. 1 and 7) possess positive e Nd (t) values varying from 0.2 to 5, and show enrichments in LILE and LREE relative to HFSE, with negative Nb-Ta anomalies, suggesting that the Late Triassic mafic-ultramafic magmas were derived from partial melting of a metasomatized lithospheric mantle triggered by upwelling asthenosphere Lü et al, 2011;Wei et al, 2013). Relative to the Middle-Late Permian (e.g., Nos.…”
Section: Petrogenesis Of the Hongqiling Mafic-ultramafic Intrusionsmentioning
confidence: 99%
“…(b) Tectonic sketch map of NE China (modified after Wilde et al, 2000;Wu et al, 2007;and Zhou and Wilde, 2013). (c) Geological map of the central area of Jilin Province (modified after Wei et al, 2013). 2006; Tang and Yang, 2007;Lü et al, 2011;Wei et al, 2013;Hao et al, 2014a, b). Due to minor occurrence of Middle-Late Permian magmatism in the CJP, the tectonic events of this stage are still poorly constrained.…”
Section: Introductionmentioning
confidence: 99%